Comments on: Effect of physical activity on long COVID fatigue - Hinpetch Daungsupawong; Viroj Wiwanitkit (PAGEPress Publications, 2023)
This correspondence discusses a published article on the effects of physical activity on Long COVID fatigue. Confounding factors are possible and should be acknowledged. When managing Long COVID-19 fatigue, you need to worry about other possible causes of the problem.